Utilization of Subcutaneous Fat from Cattle in Soap Production Technology - Kuramboev T.B; Ruziboev A.T; Kuramboev Sh.R (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article explores the potential of utilizing subcutaneous fat derived from cattle as a secondary raw material in soap production technology. The research focuses on the physicochemical properties of bovine adipose tissue and the processes required for its conversion into high-quality soap, including purification, hydrolysis, neutralization, and saponification. Technological parameters affecting soap yield and quality are analyzed, along with the environmental and economic benefits of repurposing animal by-products. Experimental results demonstrate that optimized processing of bovine subcutaneous fat can serve as a sustainable alternative to traditional fats in soap manufacturing, contributing to circular economy practices and reducing organic waste in the meat processing industry.